Anxiety and public responses to covid-19: Early data from Thailand. (October 2020) - Goodwin, Robin; Wiwattanapantuwong, Juthatip; Tuicomepee, Arunya; Suttiwan, Panrapee; Watakakosol, Rewadee
Abstract: Any new pandemic has the potential to arouse considerable anxiety, with this anxiety associated in previous work with economic disruption and societal disruption. We examined anxiety, symptom awareness, trust and associated behavioural responses in the first three weeks of the SARS-CoV-2 (covid-19) outbreak in Thailand. We collected data on-street at randomly selected locations in Bangkok. Of 274 potential respondents, 203 (74.7%) responded. A four-item measure assessed anxiety, with open-ended questions assessing knowledge of symptoms, trusted information sources and measures taken to avoid infection. Respondents reported good awareness of the prime symptoms of the Coronovirus. Binary logistic regressions controlling for sex and age found the more anxious avoided the Chinese, people who were coughing, crowded places and public transport or flying. Younger respondents reported greater trust in foreign media and older populations information from national government. Trust in doctors online was positively associated with avoidance of coughing people and keeping fit; trust in national government with avoiding coughing people, keeping fit, and avoiding public transport . We conclude that anxiety can motivate both desirable and undesirable behaviours during pandemic outbreaks. Effective and targeted communication by trusted sources is needed to motivate preventive actions but also to limit unnecessary or disruptive behaviours.